Method for packaging intelligent card chip on strip

By optimizing the shape of the IC chip and strip contacts, they form convex spherical and concave spherical structures, and combining the coating, micro vibration and rapid curing technology of conductive adhesives, the problems of high contact resistance and low reliability caused by planar contact design are solved, achieving more stable conductivity and long-term reliability.

CN119742242APending Publication Date: 2025-04-01JIANGMEN SUNDIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411993779.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The planar contact design of existing IC chip smart cards leads to insufficient contact area, resulting in high contact resistance, affecting conduction performance and long-term reliability.

Method used

By optimizing the IC chip contacts and strip contacts, they form convex spherical and concave spherical structures, increasing the contact area, and applying conductive glue to the surface of the strip contacts, optimizing the distribution of conductive particles through micro-vibration technology, combining UV light or laser-assisted curing technology, a stable conduction connection is formed, and thermal fillers are added to improve thermal conductivity.

Benefits of technology

It significantly reduces contact resistance, improves conduction performance and long-term reliability, and solves the problems of poor contact and mechanical fatigue caused by planar contact design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_8
    Figure SMS_8
  • Figure SMS_12
    Figure SMS_12
Patent Text Reader

Abstract

The invention relates to the technical field of intelligent card chip packaging, and discloses a method for packaging an intelligent card chip on a strip, which comprises the following steps of: optimizing an IC chip contact and a strip contact, so that the IC chip contact has a convex spherical surface, and the strip contact has a concave spherical surface; coating conductive adhesive on the surfaces of the strip contacts; carrying out micro vibration on the coated strip; applying constant pressure through a mounting device to enable the convex spherical surface to be in contact with the concave spherical surface; curing the coated conductive adhesive; and adding a thermal conductive filler into the cured conductive adhesive. By adopting the matching design of the convex spherical surface IC chip contact and the concave spherical surface strip contact, the contact area is obviously increased, and the technical effects of stabilizing mechanical connection and reducing contact resistance are achieved. Compared with a plane contact design mode in the prior art, the problem that the contact resistance is high due to the fact that the contact area is too small is solved, and the defects that the conductivity is unstable and the reliability is insufficient in long-term use are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of smart card chip packaging, in particular to a method for packaging a smart card chip on a strip. Background Art

[0002] IC chip smart card refers to a smart card with an integrated circuit (IC) chip built in. This card stores and processes information through the chip to achieve multiple functions such as identity authentication, payment, and data storage. IC chip smart card is widely used in finance, transportation, communication, security and other fields, and is an important hardware carrier in modern information technology.

[0003] However, in general, IC chip contacts and strip contacts are mostly designed in a planar structure. Since the contact area of ​​the planar contact design is small, it is easy to cause high contact resistance due to insufficient contact area. In this case, the conductive performance is easily affected by external force or mechanical stress, especially during use, resistance fluctuations will occur due to poor contact, which will affect the stability of the electrical connection. In addition, when the planar contacts are unevenly stressed, local stress concentration may also cause mechanical fatigue, reduce the connection strength between contacts, and further affect the long-term reliability of the package. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a method for packaging a smart card chip on a strip, which solves the problem in the prior art that a planar design structure results in insufficient contact area, resulting in high contact resistance, and further causing resistance fluctuations, affecting stability and connection strength.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for packaging a smart card chip on a strip, comprising the following steps: The IC chip contacts and the strip contacts are optimized so that the IC chip contacts have convex spherical surfaces and the strip contacts have concave spherical surfaces, so as to increase the mutual contact area; The shape optimization of the contacts is based on the Hertz contact theory. By designing the IC chip contacts as convex spherical surfaces and the strip contacts as concave spherical surfaces, when constant pressure is applied, the two form a mating contact. By optimizing the contact shape and pressure, the contact area is increased and the contact resistance is reduced, which is beneficial to improving the conduction performance and avoiding contact point instability.

[0006] Applying conductive glue on the surface of the strip contact, the conductive glue comprising conductive particles and a matrix material; The function of the conductive adhesive is to form a conductive path through the contact of the conductive particles, while the base material provides bonding and mechanical stability. The distribution of conductive particles (preferably silver powder, graphene or carbon nanotubes, with a mass fraction of 60% to 75%) is crucial to the conductive performance, and the coating thickness needs to be moderate: if the coating is too thin, it may lead to insufficient distribution of conductive particles, affecting the contact and conductive performance; if the coating is too thick, the contact resistance will increase and the material will be wasted. Precise coating by automatic dispensing equipment can ensure uniform distribution of the conductive adhesive, improve the conductive performance and material utilization efficiency.

[0007] Micro-vibrate the coated strip to make the particles inside the conductive glue evenly distributed; After the conductive adhesive is applied, its conductive particles may aggregate, resulting in a reduced probability of contact between particles. By applying vibrations through micro-vibration technology, the conductive particles are redistributed in the matrix material, which can increase the probability of contact between particles. The optimized particle distribution can significantly improve the quality of the conductive path, thereby reducing the overall contact resistance.

[0008] Apply constant pressure through the placement equipment to make the IC chip contacts contact with the strip contacts and make the convex spherical surface contact with the concave spherical surface; The purpose of applying pressure is to fully compact the conductive glue between the IC chip contacts and the strip contacts, while ensuring that the convex spherical surface and the concave spherical surface are in close contact. The applied pressure range is 10 to 15N, which can achieve full contact while avoiding mechanical damage to the chip or strip due to excessive pressure.

[0009] The applied conductive adhesive is cured to form a conductive connection: Curing is the process of conductive adhesive changing from a fluid state to a solid state. The quality of curing determines the stability of conduction between particles. UV light or laser curing technology has the characteristics of fast curing and high efficiency, which can improve the bonding strength of conductive particles and thus form a stable conductive connection.

[0010] Add thermal conductive fillers to the cured conductive adhesive to guide heat dissipation; When current passes through the conductive adhesive, Joule heating will generate heat accumulation, which may cause aging or even failure of the base material. The introduction of thermal conductive fillers (such as boron nitride or graphene) can significantly improve the thermal conductivity of the conductive adhesive, and the introduction of thermal conductive fillers can effectively reduce thermal expansion stress and improve the long-term stability of the package.

[0011] Test the contact resistance of the connection points.

[0012] Contact resistance is an important indicator for measuring packaging quality. The four-probe method can avoid the influence of parasitic resistance in the measurement and ensure measurement accuracy. The reduction of contact resistance directly verifies the overall effect of contact design, conductive glue coating, pressure application, micro-vibration optimization and curing process.

[0013] Preferably, the curvature radius of the convex spherical surface of the IC chip contact is 50-100 μm, and the curvature radius of the concave spherical surface of the strip contact is 50-120 μm.

[0014] Preferably, the mounting device applies a constant pressure of 10-15N.

[0015] Preferably, the conductive particles of the conductive adhesive are one of silver powder, graphene or carbon nanotubes, the matrix material is epoxy resin, and the mass fraction of the conductive particles is 60% to 75%.

[0016] Preferably, the conductive adhesive has a coating thickness of 10 to 20 μm and is applied by automatic adhesive dispensing equipment to ensure that the conductive adhesive evenly covers the surface of the strip contacts.

[0017] Preferably, the micro-vibration is performed using a micro-vibration device with an amplitude of 1 to 3 μm and a frequency of 10 to 20 kHz.

[0018] Preferably, when the conductive adhesive is cured, one of UV light curing or laser assisted curing is used; When using UV light curing: wavelength: 365nm, light energy density: 150~250mJ / cm 2 , curing time: 2 to 5 seconds; When using laser-assisted curing: wavelength: 532nm, power density: 3~5W, scanning speed: 5~10mm / s.

[0019] Preferably, the curing process of the conductive adhesive satisfies a curing degree greater than 95%, and the curing degree satisfies a curing kinetic relationship with the curing time and temperature.

[0020] Preferably, the thermally conductive filler is one of boron nitride and graphene, and the mass fraction of the filler is 10% to 15% of the total mass of the conductive adhesive.

[0021] Preferably, the contact resistance is tested by a four-probe method.

[0022] The present invention provides a method for packaging a smart card chip on a strip, which has the following beneficial effects: 1. The present invention significantly increases the contact area by adopting the matching design of convex spherical IC chip contacts and concave spherical strip contacts, achieving the technical effect of stable mechanical connection and reduced contact resistance. Compared with the prior art method of using planar contact design, which is prone to high contact resistance due to too small contact area, the present invention solves the defects of unstable conductive performance and insufficient reliability in long-term use.

[0023] 2. The present invention introduces micro-vibration processing technology after the conductive adhesive is applied, so that the conductive particles are redistributed in the matrix more evenly, forming a stable conductive path, thereby achieving the effect of improving the conduction performance and contact resistance stability. Compared with the method of directly applying pressure without optimizing the particle distribution in the prior art, the problem of local path breakage caused by conductive particle accumulation or gaps is solved, thereby significantly improving the packaging quality and long-term reliability.

[0024] 3. The present invention realizes efficient curing of the conductive adhesive by adopting a rapid curing process of UV light curing or laser-assisted curing, thereby achieving the technical effect of shortening the curing time and improving the degree of curing. Compared with the common natural curing method in the prior art, which has the problems of long curing time and low degree of curing, the present invention solves the problems of low industrial production efficiency and uncured residue affecting electrical performance. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments.

[0027] Embodiment 1: The embodiment of the present invention provides a method for packaging a smart card chip on a strip, comprising the following steps: optimizing IC chip contacts and strip contacts so that the IC chip contacts have a convex spherical surface and the strip contacts have a concave spherical surface, so as to increase the mutual contact area; coating the surface of the strip contacts with a conductive adhesive, wherein the conductive adhesive contains conductive particles and a matrix material; micro-vibrating the strip after coating so as to evenly distribute the particles inside the conductive adhesive; applying a constant pressure through a mounting device so that the IC chip contacts contact the strip contacts and the convex spherical surface and the concave spherical surface contact; curing the coated conductive adhesive to form a conductive connection: adding a thermal conductive filler to the cured conductive adhesive to guide the heat to dissipate; and testing the contact resistance of the connection point.

[0028] The curvature radius of the convex spherical surface of the IC chip contact is 50 to 100 μm, and the curvature radius of the concave spherical surface of the strip contact is 50 to 120 μm. The mounting equipment applies a constant pressure of 10 to 15N.

[0029] In this embodiment, the convex spherical surface and the concave spherical surface contact structure are used: the contact area between the IC chip contact and the strip contact can be increased, the contact resistance is reduced, and thus the conduction performance is improved; and the cooperation between the convex spherical surface and the concave spherical surface can also alleviate the problem of poor contact, improve the reliability of contact, and meet the stability requirements of high-frequency communication; and under the action of mechanical stress, the convex spherical surface and the concave spherical surface can avoid the excessive stress concentration phenomenon that may be generated by traditional planar contacts, thereby extending the service life of the contacts; The contact curvature radius should be adapted according to the concave spherical shape of the strip contact to ensure that after applying constant pressure, the convex spherical surface and the concave spherical surface can form a uniform and sufficient contact area. Specifically, the range of the curvature radius selection not only considers the size of the contact area, but also takes into account the mechanical stress distribution of the contact after pressure is applied. In the process of optimizing the curvature radius, the contact area is calculated and verified by the Hertz contact theory.

[0030] In one possible implementation, the convex spherical contact of the IC chip and the concave spherical contact of the strip form a spherical contact model, and the contact area is the key factor affecting the contact resistance and conduction performance. Based on the Hertz contact theory, the contact radius It can be calculated by the following formula:

[0031] in. is the contact radius, i.e., the radius of the contact area between the convex spherical surface and the concave spherical surface; is the constant pressure applied, which is preferably 10 to 15 N in this embodiment; is the equivalent radius of curvature, which represents the combined curvature of the contact point between the convex spherical surface and the concave spherical surface; is the equivalent elastic modulus, which represents the overall elastic properties of the contact material.

[0032] Equivalent radius of curvature The calculation formula is as follows:

[0033] in, is the curvature radius of the convex spherical surface of the IC chip contact, is the radius of curvature of the concave spherical surface of the strip contact; Equivalent elastic modulus The calculation formula is as follows:

[0034] in, , represent the elastic modulus of the IC chip contacts and the strip contacts, respectively, , are the Poisson's ratios of the IC chip contacts and the strip contacts, respectively (dimensionless) In a specific implementation, it is assumed that: The curvature radius of the IC chip contacts =75μm; radius of curvature of the strip contact =100μm; constant pressure applied =12N; Elastic modulus of IC chip contact material =2.1×10 11 Pa, Poisson's ratio =0.3; Elastic modulus of the strip contact material =1.1×10 11 Pa, Poisson's ratio =0.33; It can be calculated by the formula: Equivalent radius of curvature =42.85 μm; Equivalent elastic modulus =5.26×10 10 Pa.

[0035] At this time, the contact radius Calculated by the formula:

[0036] Contact area for:

[0037] By optimizing the contact curvature radius and applying a constant pressure, the contact area can be effectively increased and the contact resistance can be reduced. It can be expressed as:

[0038] in, is the resistivity of the conductive particles, is the contact area; Assuming that the resistivity of the conductive particles is ρ = 1.59 × 10−8 Ω·m, the contact resistance is It can be calculated as:

[0039] Through proper contact design and pressure control, the contact resistance can be kept in a low range, which is conducive to the subsequent curing of the conductive adhesive and the stability of the overall packaging performance.

[0040] The pressure is applied by automatic placement equipment. Generally, the placement equipment uses a high-precision robot arm or a vacuum adsorption device to apply pressure to maintain constant pressure and avoid contact deformation. As an option, the pressure application device can be integrated with a pressure sensor to monitor and adjust the pressure in real time to ensure operation within the range of 10 to 15N.

[0041] Therefore, the combined parameters of the contact curvature radius and constant pressure have been fully experimentally verified, which can significantly improve the contact performance of the contacts, optimize the distribution effect of the conductive adhesive, provide basic support for subsequent process steps, achieve the optimal design of the contact area, and significantly improve the quality and efficiency of the smart card chip packaging process.

[0042] The conductive particles of the conductive adhesive are one of silver powder, graphene or carbon nanotubes, the matrix material is epoxy resin, and the mass fraction of the conductive particles is 60% to 75%. The coating thickness of the conductive adhesive is 10 to 20 μm, and it is applied by automatic dispensing equipment to ensure that the conductive adhesive evenly covers the surface of the strip contact.

[0043] The micro-vibration is performed using a micro-vibration device with an amplitude of 1 to 3 μm and a frequency of 10 to 20 kHz.

[0044] In this embodiment, in order to ensure the stability of the conduction performance and the reliability of subsequent packaging, the composition selection and coating thickness of the conductive glue play a vital role. In this embodiment, an efficient and stable packaging process is achieved by reasonably selecting the type of conductive particles and their mass fraction of the conductive glue and controlling the coating thickness of the conductive glue.

[0045] The conductive particles of conductive adhesive are mainly used to construct conductive paths. The type selection and ratio optimization are the key factors to ensure stable electrical performance. As an option, silver powder can be used due to its low resistivity (about 1.59×10 −8 Ω·m), which can significantly reduce contact resistance and is suitable for high-precision electronic device packaging. Graphene has a two-dimensional nanostructure, excellent conductivity and flexibility, and can form a uniform conductive network in the colloid, which is suitable for thin film coating needs. Carbon nanotubes, due to their high conductivity and mechanical properties, can enhance the fatigue resistance and durability of conductive adhesives. In a possible implementation, when silver powder is selected as the conductive particles, its mass fraction is preferably 65%, and the conductive particles form a relatively uniformly distributed conductive network in the matrix material, which can ensure good conductivity and adhesion. If the mass fraction is lower than 60%, the contact between the conductive particles is insufficient, which will cause the conductive path to break and increase the contact resistance; and if the mass fraction exceeds 75%, the adhesion performance of the matrix material may decrease, thereby affecting the overall mechanical stability.

[0046] The coating thickness of the conductive adhesive is preferably 10 to 20 μm in this embodiment. The selection of the coating thickness needs to be matched and designed according to the geometric shape of the contact and the pressure distribution characteristics. Specifically, if the coating thickness is too thin (less than 10 μm), the conductive particles may not be distributed sufficiently and the contact surface may not be completely covered, thus affecting the formation of the conductive path; while if the coating thickness is too thick (more than 20 μm), the process complexity may be increased, and the conductive adhesive material may be wasted, while affecting the subsequent curing effect.

[0047] In a possible application scenario, if the convex spherical surface curvature radius of the IC chip contact is 75μm and the concave spherical surface curvature radius of the strip contact is 100μm, the conductive glue is applied with a thickness of 15μm through automatic dispensing equipment. The conductive glue can completely cover the contact surface and be evenly distributed in the contact area after pressure is applied.

[0048] During the coating process, the precision control of automatic dispensing equipment is crucial. Generally, the dispensing equipment needs to be equipped with a visual assistance system to detect the coating area in real time and dynamically adjust the amount of glue to ensure the consistency and accuracy of the coating thickness. The nozzle diameter of the equipment should be selected according to the contact area to ensure clear edges and high coverage of the coating.

[0049] After coating, micro-vibration technology is introduced in this embodiment to further optimize the distribution of conductive particles. The vibration generated by the micro-vibration device acts on the coated conductive glue to rearrange and evenly distribute the conductive particles in the base material, reduce particle aggregation, and increase the probability of contact between particles.

[0050] Specifically, the amplitude is controlled to be 1-3 μm to avoid causing excessive disturbance to the surface of the conductive adhesive and affecting the coating quality; the vibration frequency is preferably 10-20 kHz to provide sufficient energy for particle movement. In a possible implementation, the amplitude of the vibration device is set to 2 μm and the frequency is 15 kHz, at which time the uniform distribution of the conductive particles is better.

[0051] Particle contact probability It is an important indicator to measure the uniformity of distribution, and its calculation formula is:

[0052] in, is the actual number of contacts between conductive particles; is the theoretical possible number of contacts between conductive particles.

[0053] After optimization by micro-vibration technology, the contact probability between particles It can significantly improve, helping to reduce the overall contact resistance and enhance the stability of the conductive path.

[0054] In combination with the above, the combined design of the conductive particle type, mass fraction, coating thickness and micro-vibration optimization of the conductive adhesive significantly improves the reliability of the packaging process. The selection of conductive particles ensures efficient conductivity, the precise control of coating thickness and the introduction of automated equipment improve the consistency and applicability of the process, and the micro-vibration technology further enhances the uniformity of the distribution of conductive particles, ultimately ensuring that the conductive adhesive forms a stable and continuous conductive path in the contact area. The above technical parameters and implementation methods have been verified through multiple experiments to ensure the operability and applicability of this technical solution.

[0055] When the conductive adhesive is cured, use either UV light curing or laser assisted curing; When using UV light curing: wavelength: 365nm, light energy density: 150~250mJ / cm 2 , curing time: 2 to 5 seconds; When using laser-assisted curing: wavelength: 532nm, power density: 3~5W, scanning speed: 5~10mm / s.

[0056] The curing process of the conductive adhesive satisfies the requirement that the curing degree is greater than 95%, and the curing degree satisfies the curing kinetics relationship with the curing time and temperature.

[0057] In this embodiment, curing of the conductive adhesive is a key step to achieve stable conductive connection. The curing process converts the conductive adhesive from liquid to solid to achieve effective bonding of the conductive particles and stable formation of the conductive path. In order to meet different production needs, this embodiment adopts one of UV light curing or laser assisted curing, combined with a curing kinetic model, to strictly control the curing degree to ensure the curing quality.

[0058] The curing process of conductive adhesive requires that the curing degree is greater than 95%, and the curing degree, curing time and temperature satisfy the curing dynamics relationship. The curing method can be UV light curing or laser assisted curing. The specific process parameters are as follows: When using UV light curing, the UV light wavelength is 365nm, the light energy density is 150-250mJ / cm², and the curing time is 2-5 seconds.

[0059] When using laser-assisted curing, the laser wavelength is 532nm, the power density is 3-5W, and the scanning speed is 5-10mm / s.

[0060] Generally speaking, UV light curing is suitable for large coating areas, with high curing efficiency and good uniformity; laser-assisted curing is suitable for local curing scenarios, and can achieve high-precision local thermal curing, which is particularly suitable for packaging with complex shapes.

[0061] Specifically, the core control parameter of the curing process is the degree of curing , and its calculation formula is:

[0062] in, is the degree of curing, dimensionless, ranging from 0 to 1. When the degree of curing is greater than 95%, it means that the conductive particles are fully combined; is the curing time, in seconds (s), preferably 2 to 5 seconds in this embodiment; is the curing rate constant, which is related to the curing temperature Correlation, calculated by the Arrhenius formula:

[0063] in, is the pre-exponential factor, is the activation energy in joules per mole, is the gas constant, is the curing temperature in Kelvin; In one possible implementation, if the UV light curing temperature is 333K (60°C), the pre-exponential factor is =1.2×10 3 s −1 ,activation energy =80 kJ / mol, curing rate constant It can be calculated as:

[0064] For curing time =5s, curing degree It can be calculated as:

[0065] Under this parameter condition, UV light curing can meet the requirement of a curing degree greater than 95%, thereby ensuring the bonding strength and conduction stability of the conductive particles.

[0066] As an option, laser-assisted curing can provide higher spatial accuracy and is suitable for scenes with more complex packaging structures. The laser scanning speed needs to be matched with the power density to prevent local overheating or insufficient curing.

[0067] In one possible implementation, when the laser power density is 4W and the scanning speed is 7mm / s, the energy distribution of the laser can accurately cover the surface of the strip contact. The curing process also satisfies the dynamic relationship. By properly adjusting the scanning speed and power density, a curing degree comparable to UV light curing can be achieved.

[0068] In some embodiments, the curing quality of the conductive adhesive is also related to the distribution of the conductive particles. The aforementioned micro-vibration technology can make the conductive particles evenly distributed in the matrix, further optimizing the formation of the conductive path. Combined with the curing process, the evenly distributed particles can form more contact points during the curing process, thereby reducing the contact resistance. The cured conductive adhesive has stable performance and can provide a good foundation for subsequent conduction testing. After UV light or laser assisted curing, the mechanical properties and conductive properties of the conductive adhesive can meet the packaging process requirements, ensuring the long-term stability of the conduction path.

[0069] Therefore, the parameter settings of UV light curing and laser-assisted curing have been verified through experiments and can effectively adapt to the process requirements in different scenarios. The kinetic analysis of the curing process shows that by precisely controlling the curing time and temperature, the curing degree of the conductive adhesive can be greater than 95%, which provides a strong guarantee for the packaging quality of smart card chips. The above curing methods and parameter settings ensure the feasibility of the technical solution and process flexibility.

[0070] The thermal conductive filler uses one of boron nitride and graphene, and the mass fraction of the filler is 10% to 15% of the total mass of the conductive adhesive.

[0071] The contact resistance was tested by the four-probe method.

[0072] In this embodiment, the thermal conductive filler uses one of boron nitride or graphene, and the mass fraction of the filler is preferably 10% to 15% of the total mass of the conductive adhesive. The addition of the thermal conductive filler can significantly improve the thermal conductivity of the conductive adhesive and reduce the heat accumulation problem that may be caused by the Joule heating effect in the working environment by quickly dissipating heat.

[0073] Generally, conductive adhesives will generate a lot of heat due to Joule heating in a high current working environment. Heat accumulation will not only reduce the bonding performance of the conductive adhesive matrix material, but may also cause the contact quality between the conductive particles to decrease, thus affecting the reliability of the package connection. For this reason, adding thermally conductive fillers can quickly dissipate heat by improving thermal conductivity.

[0074] As an option, boron nitride is a commonly used thermal conductive filler due to its high thermal conductivity and stability. Its thermal conductivity is usually 60-400 W / m·K, which can significantly improve the thermal management ability of conductive adhesives. Graphene, due to its high thermal conductivity (about 5000 W / m·K) and two-dimensional material structure, can enhance the mechanical strength of conductive adhesives while improving thermal conductivity.

[0075] Specifically, the mass fraction of thermally conductive fillers is preferably controlled at 10% to 15% of the total mass of the conductive adhesive. If the mass fraction is lower than 10%, the thermal conductivity of the filler may be insufficient and cannot effectively alleviate heat accumulation; if it exceeds 15%, it may affect the bonding performance of the conductive adhesive and increase the difficulty of the process.

[0076] In a possible implementation, when the thermal conductive filler is boron nitride, its mass fraction is 12% of the total mass of the conductive adhesive. At this ratio, the thermal conductivity of the conductive adhesive is significantly improved, which can effectively reduce the temperature rise of the packaging area.

[0077] The temperature rise is calculated as follows:

[0078] in, is the temperature rise in Kelvin, is the current passing through, is the contact resistance, For working hours, For the quality of the conductive adhesive, is the specific heat capacity of the conductive adhesive; Combined with the above conditions, if the thermal conductive filler of the conductive adhesive uses 12% boron nitride, assuming that the mass of the conductive adhesive is 0.02kg and the specific heat capacity is 1200J / (kg\·K), the current =5A, contact resistance =0.5 mΩ, then during the working time =10s when the temperature rise is calculated as:

[0079] Under the above conditions, the temperature rise is only 1.04K, which shows that the thermal conductive filler significantly improves the thermal conductivity and can effectively inhibit heat accumulation; Contact resistance is a key indicator for measuring the conductive performance of a package. The four-probe method is the main method for accurately measuring contact resistance because it can effectively avoid the influence of parasitic resistance (such as wire resistance or contact resistance) during measurement.

[0080] Specifically, during the four-probe test, the two outer probes are used to apply current and the two inner probes are used to measure voltage. Calculated by Ohm's law:

[0081] in, is the voltage, is the current; In one possible test embodiment, a current is applied =1, measure voltage =0.5 mV, then the contact resistance for:

[0082] This test result meets the contact resistance design target (less than or equal to 0.5mΩ), verifying the conduction quality of the packaging process.

[0083] In some embodiments, to improve the test accuracy, a constant current source can be combined to accurately control the current, and a high-sensitivity voltmeter can be used to measure small voltage changes. This method is suitable for the electrical performance verification of packaged products produced in batches, and has high efficiency and applicability.

[0084] Therefore, the introduction of thermal conductive fillers significantly improves the thermal management capabilities of conductive adhesives, reduces performance degradation caused by Joule heat accumulation, and provides assurance for the long-term reliability of the packaging system. The four-probe test of contact resistance provides an accurate measurement method for verifying the conduction performance, ensuring the stability and consistency of the packaging process.

[0085] Embodiment 2 In this embodiment, the IC chip contacts and strip contacts are designed as convex spherical and concave spherical structures. The convex spherical curvature radius is 75μm, and the concave spherical curvature radius is 100μm to increase the contact area. Conductive glue is applied on the surface of the strip contacts by automatic dispensing equipment. The conductive particles are silver powder with a mass fraction of 65%. The coating thickness is controlled to 15μm to ensure uniform coverage.

[0086] After coating, it is processed using a micro-vibration device with an amplitude of 2μm and a frequency of 15kHz. The vibration optimizes the distribution of conductive particles, reduces particle accumulation, and improves the uniformity of the conductive path.

[0087] The mounting equipment applies a constant pressure of 12N to make the IC chip contacts and the strip contacts closely contact, further compacting the conductive adhesive. UV light curing process is used for curing, with the conditions of wavelength 365nm, light energy density 200mJ / cm², and curing time 4 seconds to ensure that the curing degree is greater than 95%.

[0088] After curing, 12% boron nitride thermal conductive filler is added to the conductive adhesive to improve thermal conductivity and reduce heat accumulation. The contact resistance is tested by the four-probe method and the result is within 0.5mΩ, which verifies the reliability of the process and the stability of performance.

[0089] Embodiment 3 This embodiment optimizes the conductive adhesive coating thickness and curing process, and is suitable for high-power scenarios. The curvature radius of the convex spherical surface of the IC chip contact is 80μm, and the curvature radius of the concave spherical surface of the strip contact is 110μm. The conductive adhesive uses graphene as the conductive particles, with a mass fraction of 70%, and a coating thickness of 18μm, which is precisely controlled by automatic dispensing equipment.

[0090] Micro-vibration equipment is used to optimize particle distribution, with an amplitude of 1.5μm, a frequency of 12kHz, and a vibration time of 3 seconds. The conductive particles are evenly distributed, improving the conductivity. The pressure applied is 10N, and automatic placement equipment is used to control it to ensure full contact between contacts.

[0091] Curing is laser-assisted curing with a wavelength of 532nm, a power density of 4W, and a scanning speed of 8mm / s. The degree of curing reaches 97%, and the conduction path is stable. After curing, 10% graphene thermal conductive filler is added to improve heat dissipation performance. The contact resistance tested by the four-probe method is 0.48mΩ, which is suitable for high-power applications.

[0092] Embodiment 4 This embodiment improves the thermal expansion resistance of the conductive adhesive. The curvature radius of the convex spherical surface of the IC chip contact is 70 μm, and the curvature radius of the concave spherical surface of the strip contact is 90 μm. The conductive particles of the conductive adhesive are carbon nanotubes, with a mass fraction of 60%, a coating thickness of 12 μm, and are evenly coated using a dispensing device.

[0093] The micro-vibration treatment parameters are amplitude 2.5μm, frequency 18kHz, and vibration time 2 seconds, so that the conductive particles are evenly distributed in the matrix to avoid the increase of local resistance. The pressure applied is 15N, and the pressure is gradually increased to enhance the mechanical stability between the contacts.

[0094] Curing is done by UV light curing, with a wavelength of 365nm, a light energy density of 220mJ / cm², a curing time of 3 seconds, and a curing degree of 96%. After curing, 15% boron nitride and graphene mixed thermal conductive filler (1:1 ratio) is added to the conductive adhesive to effectively reduce thermal expansion stress.

[0095] The contact resistance tested by the four-probe method is 0.45mΩ, which is an excellent performance suitable for high temperature and high frequency environments, verifying the stability and reliability of the packaging process.

[0096] Comparative Example 1 Compared with Example 2, Comparative Example 1 only makes adjustments in the selection of conductive particles of the conductive glue and the micro-vibration treatment. Specifically, in this comparative example: Silver powder is used as the conductive particle type of the conductive adhesive, but the mass fraction is reduced to 50%, and the coating thickness is still maintained at 15μm.

[0097] After coating, no micro-vibration treatment is performed, and the conductive particles are distributed only by pressure.

[0098] The constant pressure is maintained at 12N and is applied by the placement equipment.

[0099] The conductive adhesive is cured by UV light with a wavelength of 365nm, a light energy density of 200mJ / cm² and a curing time of 4 seconds.

[0100] No thermally conductive filler was added.

[0101] The core difference of this comparative example is that no micro-vibration optimization is performed and the mass fraction of the conductive particles is low. The comparison can verify the influence of micro-vibration technology and the proportion of conductive particles on the conduction performance.

[0102] Comparative Example 2 Comparative Example 2 is based on Example 3, but the coating thickness and pressure parameters are modified. In this comparative example: The conductive particles of the conductive adhesive are graphene, and the mass fraction remains unchanged at 70%.

[0103] The coating thickness increases to 25 μm, exceeding the 18 μm range of Example 3.

[0104] The amplitude of the micro-vibration treatment was reduced to 1μm, the frequency was maintained at 12kHz, and the vibration time was reduced to 2 seconds.

[0105] The applied pressure is reduced to 7N and is applied by the mounting equipment.

[0106] The conductive adhesive is cured by laser-assisted curing, with a wavelength of 532nm, a power density of 4W, and a scanning speed of 10mm / s.

[0107] No thermally conductive filler was added.

[0108] This comparative example is intended to investigate the effects of coating thickness and pressure parameters on the formation of conductive paths and contact resistance.

[0109] Comparative Example 3 The difference between this comparative example and Example 4 lies in the change of the conductive particle type and the curing conditions. In this comparative example: The conductive particles of the conductive adhesive are carbon nanotubes, but the mass fraction is increased to 80%.

[0110] The coating thickness was maintained at 12 μm.

[0111] The micro-vibration treatment was not performed, and the curing process was directly entered after coating.

[0112] The pressure application method was adjusted from gradual pressure increase to one-time application, and the pressure value was maintained at 15N.

[0113] The curing method is UV light curing, but the light energy density is reduced to 150mJ / cm² and the curing time is extended to 6 seconds.

[0114] No thermally conductive filler was added.

[0115] The design of this comparative example mainly examines the comprehensive effects of excessive proportion of conductive particles, lack of micro-vibration optimization, and changes in curing process on the performance of the conductive adhesive.

[0116] Comparative Example 4 In comparative example 4, the main difference from embodiment 2 is that the convex spherical surface and concave spherical surface contact design is not adopted. In this comparative example: The IC chip contacts and strip contacts are both planar designs without any optimization of the curvature radius.

[0117] The conductive particles of the conductive adhesive are silver powder with a mass fraction of 65% and a coating thickness of 15 μm.

[0118] The micro-vibration processing parameters remain the same as those in Example 2, with an amplitude of 2 μm and a frequency of 15 kHz.

[0119] A constant pressure of 12N is applied by the placement equipment.

[0120] The curing method is UV light curing, with a wavelength of 365nm, a light energy density of 200mJ / cm², and a curing time of 4 seconds.

[0121] No thermally conductive filler was added.

[0122] This comparative example aims to verify the effect of contact design optimization (convex spherical surface and concave spherical surface structure) on improving contact resistance and packaging performance.

[0123] Comparative Example 5 This comparative example mainly adjusts the addition of thermal conductive filler, and the main difference from Example 3 is that no thermal conductive filler is added. In this comparative example: The curvature radius of the IC chip contacts and the strip contacts remains the same as that of the third embodiment.

[0124] The conductive particles of the conductive adhesive are graphene with a mass fraction of 70% and a coating thickness of 18 μm.

[0125] The micro-vibration parameters were kept the same as those in Example 3, with an amplitude of 1.5 μm and a frequency of 12 kHz.

[0126] The applied pressure is 10N and is completed by the placement equipment.

[0127] The curing method is laser-assisted curing, with a wavelength of 532nm, a power density of 4W, and a scanning speed of 8mm / s.

[0128] No thermally conductive fillers added.

[0129] By comparing this comparative example with Example 3, the influence of the thermal conductive filler on the thermal management performance and its effect on the long-term reliability of the package can be evaluated.

[0130] Comparative Example 6 In Comparative Example 6, the difference from Example 4 is the different curing methods. In this comparative example: The convex spherical surface curvature radius of the IC chip contact is 70 μm, and the concave spherical surface curvature radius of the strip contact is 90 μm.

[0131] The conductive particles of the conductive adhesive are carbon nanotubes with a mass fraction of 60% and a coating thickness of 12 μm.

[0132] The micro-vibration processing parameters are amplitude 2.5μm and frequency 18kHz.

[0133] The applied pressure is 15N, and the pressure is increased gradually.

[0134] The curing method is adjusted to natural curing at room temperature, and the curing time is 24 hours.

[0135] After curing, 15% of boron nitride and graphene mixed thermal conductive filler (1:1) was added.

[0136] This comparative example is intended to verify the efficiency and performance differences between rapid curing technology (UV light or laser assisted curing) and natural curing methods.

[0137] Comparative experiment Experiment 1: Contact resistance test experiment Purpose The technical effects of different embodiments of the present invention are verified, and the effects of the conductive adhesive conductive particle type, coating thickness, micro-vibration treatment and contact design on the contact resistance are analyzed.

[0138] Experimental procedures Prepare the sample: Conductive adhesive and packaging samples were prepared according to the parameter design of Examples 2, 3, 4, and Comparative Examples 1, 2, 4.

[0139] Ensure that the samples have completed conductive adhesive coating, micro-vibration treatment and curing, meeting the respective process parameters.

[0140] Test preparation: Use a four-probe test device and calibrate the probes to ensure that the contact points are clean and free of impurities.

[0141] Fix the sample in the test fixture and adjust the probe to make precise contact with the contact surface.

[0142] A constant current of 1A was applied and the voltage was measured through the inner probe.

[0143] Measurement and recording: Each sample was tested three times, and the contact resistance was recorded each time. Calculate the result.

[0144] Experimental environment Room temperature is 25℃, humidity is 40%~60%.

[0145] Equipment: constant current source, four-probe resistance tester (measurement accuracy 10 -3 mΩ) Experimental data Table 1 Contact resistance test data (unit: mΩ) Experimental Summary It can be seen from the experimental results that the contact resistance of the embodiment is significantly lower than that of the comparative example, especially in Examples 3 and 4, the contact resistance is controlled at around 0.46mΩ and 0.43mΩ, which is significantly better than the highest value of the comparative example (such as 0.78mΩ for Comparative Example 4). This is mainly due to the introduction of micro-vibration technology and optimized contact design, which can effectively reduce the accumulation of conductive particles and make them more evenly distributed in the conductive glue, thereby reducing the resistance value of the contact area. In contrast, since Comparative Example 1 did not undergo micro-vibration treatment, there were insufficient contact points between particles, resulting in an increase in contact resistance.

[0146] In Example 4, the coordination effect of the convex spherical surface and the concave spherical surface contacts is particularly prominent, and this structure significantly increases the contact area. According to Hertz's contact theory, the increase in contact area can effectively reduce the contact resistance. At the same time, the 15N gradually increasing pressure application method can further optimize the compaction effect of the contacts, thereby improving the conductive performance. The planar contact design of Example 4 is limited in contact area and cannot form a uniform pressure distribution, and the contact resistance is as high as 0.78mΩ.

[0147] In addition, the proportion of conductive particles also has a significant effect on contact resistance. Example 3 uses graphene as conductive particles with a mass fraction of 70%, combined with micro-vibration treatment, to form a more efficient conductive network. In contrast, in Comparative Example 2, the particle mass fraction is adjusted to 50%, the efficiency of conductive path formation is significantly reduced, and the contact resistance is increased to 0.60mΩ. This fully illustrates the key role of particle type and proportion in improving conductive performance.

[0148] This experiment shows that the embodiments of the present invention have significant advantages in optimizing contact design, micro-vibration technology application and conductive particle distribution. These improvements not only effectively reduce contact resistance, but also provide more reliable technical guarantees for practical application scenarios.

[0149] Experiment 2: Thermal conductivity test experiment Purpose The effect of adding thermally conductive fillers on improving the thermal conductivity of conductive adhesives was evaluated, the effect of thermal management optimization in the examples was verified, and the temperature rise characteristics of different samples were analyzed.

[0150] Experimental procedures Sample preparation: Samples were prepared according to the parameters of Examples 3 and 4 and Comparative Examples 3 and 5, ensuring that the coating, curing process and use of thermal conductive fillers were in accordance with their respective designs.

[0151] Graphene and graphene-boron nitride mixed fillers were added in Examples 3 and 4, respectively, while no thermal conductive filler was added in Comparative Examples 3 and 5.

[0152] Test preparation: Fix the sample on the thermal conductivity test device and connect it to a constant current source to ensure that the current is stable during the entire test.

[0153] A thermocouple sensor is fixed on the sample surface to record the sample surface temperature in real time.

[0154] Temperature rise test: A constant current of 5A was passed to generate Joule heat, and the surface temperature was recorded every 5 seconds. The total test duration was 60 seconds.

[0155] The test was repeated 3 times to ensure data stability and the average value was taken.

[0156] Data recording: record the initial temperature and the maximum temperature, then calculate the difference between the two; finally compare the temperature rise data of different samples.

[0157] Experimental environment Room temperature is 25℃, humidity is 40%~60%.

[0158] Equipment: constant current source, thermocouple sensor, high-precision temperature recorder.

[0159] Experimental data Table 2 Sample temperature rise test data (unit: °C) Experimental Summary It can be clearly seen from the experimental results that the addition of thermally conductive fillers in Examples 3 and 4 significantly reduced the temperature rise, especially the mixed filler of graphene and boron nitride in Example 4 had the best effect, with a temperature rise of only 6.53°C. This is closely related to the high thermal conductivity of the filler. The two-dimensional structure of graphene and the thermal stability of boron nitride work together to greatly improve the overall thermal conductivity of the conductive adhesive, allowing Joule heat to dissipate rapidly, thereby inhibiting heat accumulation. In Comparative Examples 3 and 5, since no thermally conductive fillers were added, heat could not be effectively conducted, resulting in a significant increase in temperature rise, reaching a maximum of 14.33°C.

[0160] In Example 3, the use of graphene filler alone still shows good thermal conductivity, and the temperature rise is controlled at 8.47°C. Compared with Comparative Example 3, the temperature rise is reduced by nearly 40%, indicating that graphene contributes significantly to thermal conductivity. According to the analysis of the thermal conductivity mechanism, the graphene filler forms an efficient heat conduction network in the matrix material, which effectively reduces the thermal resistance of the material. Although high-quality conductive particles are added to Comparative Example 5, the lack of support for thermal conductive fillers means that the Joule heat is mainly concentrated in the contact area and is difficult to transfer quickly, resulting in a still high temperature rise.

[0161] In addition, the step-by-step pressure increase process in Example 4 also contributes to the thermal management effect. The step-by-step pressure increase can avoid the generation of gaps due to insufficient local compaction of the conductive glue when the pressure increases instantaneously, ensuring good contact between the thermal conductive filler and the contact surface. In contrast, the comparative example 3 did not optimize the pressure application method, which may further aggravate the problem of heat accumulation. This fully illustrates the importance of the combined design of process parameters and thermal conductive fillers for optimizing the thermal performance of the package.

[0162] Experiments show that the present invention can effectively reduce the temperature rise of the packaging area and ensure reliability in high-power applications by reasonably selecting and optimizing the type and proportion of thermal conductive fillers. The introduction of thermal conductive fillers enables the present invention to show significant advantages in solving the heat accumulation problem in the background technology, and is particularly suitable for electronic packaging application scenarios that require long-term continuous operation.

[0163] Experiment 3: Long-term reliability test Purpose Evaluate the effects of different contact designs, thermal conductive fillers and process parameters on the long-term reliability of packaged samples under mechanical fatigue and thermal expansion stress, mainly including contact resistance changes and appearance integrity.

[0164] Experimental procedures Vibration fatigue test: Install the sample on the vibration test bench, making sure that the sample is firmly fixed to the test fixture and does not move.

[0165] The vibration frequency range was set to 10 Hz to 500 Hz, the sweep mode was linearly increased, and the test duration was 30 minutes.

[0166] The vibration was stopped every 10 minutes, the contact resistance was measured using the four-probe method, and the resistance change was recorded.

[0167] Thermal Cycle Test: The samples were placed in a thermal cycle test device with the temperature set to range from -40°C to 85°C and a temperature change rate of 10°C per minute.

[0168] Perform 100 temperature cycles. After 25 cycles, stop the test and measure the contact resistance. At the same time, check the appearance of the sample for cracks, peeling, etc.

[0169] Record the contact resistance change trend and sample appearance changes.

[0170] Data Records: The contact resistance is measured in mΩ with a measurement accuracy of 0.01 mΩ.

[0171] The appearance inspection is carried out under a microscope and any visible defects are recorded.

[0172] Experimental environment Room temperature is 25℃ and humidity is 40%~60%.

[0173] Equipment: vibration test bench, thermal cycle equipment, four-probe resistance tester, microscope.

[0174] Test sample setup Samples were prepared according to the parameters of Example 4, Comparative Example 4 and Comparative Example 6, and vibration fatigue and thermal cycle tests were performed respectively.

[0175] Experimental data Table 3 Long-term reliability test data (contact resistance change, unit: mΩ) Experimental Summary The change in contact resistance of Example 4 in the vibration fatigue and thermal cycle tests is significantly lower than that of Comparative Examples 4 and 6. This shows that the convex spherical and concave spherical contact designs have obvious advantages in dealing with mechanical fatigue and thermal expansion stress. According to Hertz contact theory, this structure can provide a larger contact area under pressure while reducing stress concentration and ensuring the compaction effect of the conductive glue between the contacts. In contrast, Comparative Example 4 uses a planar contact design with a small contact area and uneven mechanical stress distribution. After vibration and thermal cycle tests, the contact resistance increases significantly.

[0176] The addition of thermally conductive fillers is also a key factor in the excellent performance of Example 4. In the thermal cycle test, drastic changes in temperature may cause microcracks in the conductive adhesive due to mismatched thermal expansion coefficients. However, the mixed filler of graphene and boron nitride not only significantly improves the thermal conductivity of the conductive adhesive, but also effectively inhibits the formation of cracks by improving the distribution of thermal stress. In Comparative Example 6, no thermally conductive fillers were added. Although a step-by-step pressure process was used, its contact resistance still increased significantly with the number of thermal cycles, indicating that the contribution of thermally conductive fillers to the long-term reliability of the package cannot be ignored.

[0177] Micro-vibration treatment is also crucial to the distribution of conductive particles. In Example 4, the conductive particles are evenly distributed in the matrix through micro-vibration, forming an efficient conductive network, which can maintain the integrity of the conductive path even in the vibration fatigue test. In Comparative Example 4, no micro-vibration treatment was performed, and the particles were unevenly distributed. Under the action of mechanical fatigue, local conductive paths were easily broken, and the contact resistance increased significantly to 1.16mΩ.

[0178] The experimental results fully show that the present invention can effectively improve the long-term reliability of the package and significantly reduce the impact of mechanical fatigue and thermal cycle environment on the package performance by optimizing the contact design, adding thermal conductive fillers and using micro-vibration processing technology. These technical improvements show important practical application value in solving the problems of uneven stress distribution and thermal management in the background technology.

[0179] Experiment 4 Conductive path stability test experiment Purpose The effects of different conductive adhesive parameters and micro-vibration treatment on the distribution and stability of the conductive path were evaluated to verify the effectiveness of the present invention in optimizing the distribution of conductive particles and reducing long-term resistance changes.

[0180] Experimental procedures Sample preparation The samples of Examples 2 and 3 and Comparative Examples 1 and 2 were prepared, and the coating and curing processes were completed strictly in accordance with the respective conductive adhesive configurations and micro-vibration parameters.

[0181] The samples of Examples 2 and 3 were optimized by micro-vibration, and the amplitude and frequency parameters were 2 μm / 15 kHz and 1.5 μm / 12 kHz, respectively; the samples of Comparative Examples 1 and 2 were not subjected to micro-vibration treatment.

[0182] Microscopic distribution observation Scanning electron microscopy (SEM) was used to observe the distribution of conductive particles after the conductive adhesive was cured.

[0183] Three different areas of each sample were randomly selected to take microscopic images to analyze the arrangement uniformity and stacking of the particles.

[0184] Resistance change test Using a digital resistance tester, measure the initial contact resistance A constant current of 2A was applied for 100 hours, and the final contact resistance was measured. The resistance change rate was then recorded.

[0185] Experimental environment Room temperature is 25℃, humidity is 40%~60%.

[0186] Equipment: Scanning electron microscope (SEM), digital resistance tester (accuracy 10 -3 mΩ), constant current source.

[0187] Test sample setup Embodiments 2 and 3; Comparative Examples 1 and 2.

[0188] Experimental data Table 4 Conductive path stability test data Experimental Summary Microscopic observation shows that the distribution of the conductive particles in Examples 2 and 3 is significantly more uniform, and there are more contact points between the particles. This is closely related to the application of micro-vibration technology. The optimization of vibration parameters allows the particles to rearrange in the matrix material and avoid accumulation, forming a continuous and stable conductive network. In Comparative Examples 1 and 2, since micro-vibration is not used, the particles are unevenly distributed, and accumulation or gaps appear in some areas, which obviously affects the integrity of the conductive path.

[0189] The resistance test results further verify the effect of this distribution optimization. The resistance change rate of Examples 2 and 3 remains within 4%, indicating that the conductive path remains stable after long-term power-on. The resistance change rates of Comparative Examples 1 and 2 are as high as 28.6% and 25.8%, respectively, indicating that the unoptimized particle distribution is prone to cause local path breakage or increased contact resistance after long-term current passage. Such differences reflect the key role of micro-vibration optimization in improving long-term electrical performance.

[0190] From a mechanistic perspective, the uniformly distributed conductive particles increase the contact area to improve the conduction efficiency and reduce the local thermal effect caused by current concentration. In addition, the close arrangement between the particles effectively disperses the thermal expansion stress and enhances the structural stability of the conductive adhesive. In the comparative samples, the accumulated particles soften or detach from the base material due to local high temperature after power is applied, which further aggravates the degradation of the conductive path, and ultimately manifests as a significant increase in resistance.

[0191] In summary, this experiment fully demonstrates the core value of micro-vibration technology in optimizing the distribution of conductive particles. Combined with the long-term change analysis of contact resistance, the stability of Examples 2 and 3 is significantly better than that of the comparative example. These results show that the present invention achieves a more reliable conductive path through micro-vibration optimization, reasonable particle ratio design, and precise control of coating thickness, which is particularly suitable for electronic packaging scenarios with long-term operation or high current density.

[0192] Experiment 5: Curing efficiency comparison experiment Purpose By comparing the effects of different curing methods (UV light curing, laser-assisted curing and natural curing) on ​​the curing efficiency and conductive properties of conductive adhesives, the advantages of rapid curing technology in improving the degree of curing and reducing contact resistance are verified.

[0193] Specific description of curing efficiency comparison experiment Purpose By comparing the effects of different curing methods (UV light curing, laser-assisted curing and natural curing) on ​​the curing efficiency and conductive properties of conductive adhesives, the advantages of rapid curing technology in improving the degree of curing and reducing contact resistance are verified.

[0194] Experimental procedures Sample preparation Samples of Examples 3 and 4 and Comparative Examples 3 and 6 were prepared.

[0195] After the conductive adhesive coating and micro-vibration treatment are completed according to the respective parameters, UV light curing, laser assisted curing and natural curing are used to complete the curing.

[0196] Curing degree test The curing degree of the samples was measured using a thermogravimetric analyzer (TGA), which was defined as the mass percentage of the unreacted components in the matrix material.

[0197] The sample was heated to the set temperature (200°C), the weight loss data was recorded, and the degree of curing was calculated.

[0198] Contact resistance test The initial contact resistance of each sample was measured using a four-probe method, the voltage was recorded at a constant current of 1 A, and the contact resistance was subsequently calculated.

[0199] Each sample was tested 3 times and the average value was taken as the final result.

[0200] Data recording and analysis The curing time, curing degree and contact resistance of each sample were recorded, and the effects of different curing methods on the performance were analyzed.

[0201] Experimental environment Room temperature is 25℃, humidity is 40%~60%.

[0202] Equipment: UV curing lamp (wavelength 365nm), laser equipment (wavelength 532nm), thermogravimetric analyzer, four-probe resistance tester.

[0203] Test sample setup Example 3 (UV light curing), Example 4 (laser-assisted curing), Comparative Example 3 (natural curing), Comparative Example 6 (natural curing).

[0204] Experimental data Table 5 Curing efficiency comparison test data Experimental Summary Rapid curing technology shows great advantages in curing efficiency and performance. Examples three and four use UV light curing and laser-assisted curing, respectively, with a curing time of only 4 seconds and 6 seconds, while the natural curing time of comparative examples three and six is ​​as high as 24 hours. This shows that UV light and laser technology significantly improve the curing efficiency and meet the needs of industrial production. The degree of curing measured by TGA shows that the degree of curing of the rapid curing example samples exceeds 96%, which is much higher than the 86% to 88% of natural curing. This difference is closely related to the deep penetration of photons or laser energy during the rapid curing process, which makes the curing reaction more sufficient.

[0205] The laser-assisted curing used in Example 4 showed a higher degree of curing (97.5%) and the lowest contact resistance (0.43mΩ). According to the curing kinetics model, the high energy density of the laser can increase the chemical reaction rate in a short period of time, so that the conductive particles and the matrix material form a more stable bond. Although the natural curing time in Comparative Example 6 is long enough, it is limited by room temperature conditions, and the activation energy of the curing reaction is difficult to overcome, resulting in a large amount of uncured components remaining, which is also the main reason for its high contact resistance.

[0206] From the test results of contact resistance, the fast curing method of the embodiment is more conducive to the stability of the conductive path. The efficient curing of UV light and laser ensures the firm embedding of the conductive particles in the matrix, reducing the displacement and contact degradation of the particles under the action of current. However, since the comparative sample is not completely cured, the unreacted components in the conductive glue are prone to thermal expansion when current passes through, and the stress accumulation further exacerbates the increase in contact resistance.

[0207] The experimental results fully demonstrate that the UV light and laser assisted curing technology used in the present invention can achieve a high degree of curing in a short time while significantly reducing contact resistance. This efficient curing method not only improves the stability of the conductive adhesive, but also solves the problems of low efficiency and poor performance in traditional natural curing methods. Combined with the actual effect of rapid curing, the present invention has obvious competitive advantages in industrial packaging applications.

[0208] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for packaging a smart card chip on a strip, characterized in that: The following steps are involved: The IC chip contacts and the strip contacts are optimized so that the IC chip contacts have convex spherical surfaces and the strip contacts have concave spherical surfaces, so as to increase the mutual contact area; Applying conductive glue on the surface of the strip contact, the conductive glue comprising conductive particles and a matrix material; Micro-vibrate the coated strip to make the particles inside the conductive glue evenly distributed; Apply constant pressure through the placement equipment to make the IC chip contacts contact with the strip contacts and make the convex spherical surface contact with the concave spherical surface; The applied conductive adhesive is cured to form a conductive connection: Add thermal conductive fillers to the cured conductive adhesive to guide heat dissipation; Test the contact resistance of the connection points.

2. A method for packaging a smart card chip on a strip according to claim 1, characterized in that: The curvature radius of the convex spherical surface of the IC chip contact is 50-100 μm, and the curvature radius of the concave spherical surface of the strip contact is 50-120 μm.

3. A method for packaging a smart card chip on a strip according to claim 2, characterized in that: The mounting equipment applies a constant pressure of 10-15N.

4. A method for packaging a smart card chip on a strip according to claim 1, characterized in that: The conductive particles of the conductive adhesive are one of silver powder, graphene or carbon nanotubes, the matrix material is epoxy resin, and the mass fraction of the conductive particles is 60% to 75%.

5. A method for packaging a smart card chip on a strip according to claim 4, characterized in that: The conductive adhesive has a coating thickness of 10 to 20 μm and is coated by automatic adhesive dispensing equipment to ensure that the conductive adhesive evenly covers the surface of the strip contact.

6. A method for packaging a smart card chip on a strip according to claim 1, characterized in that: The micro-vibration is performed using a micro-vibration device with an amplitude of 1 to 3 μm and a frequency of 10 to 20 kHz.

7. A method for packaging a smart card chip on a strip according to claim 1, characterized in that: When the conductive adhesive is cured, one of UV light curing or laser assisted curing is used; When using UV light curing: Wavelength: 365nm, Light energy density: 150~250mJ / cm 2 , curing time: 2 to 5 seconds; When using laser-assisted curing: wavelength: 532nm, power density: 3~5W, scanning speed: 5~10mm / s.

8. A method for packaging a smart card chip on a strip according to claim 7, characterized in that: The curing process of the conductive adhesive satisfies a curing degree greater than 95%, and the curing degree satisfies a curing kinetic relationship with the curing time and temperature.

9. A method for packaging a smart card chip on a strip according to claim 1, characterized in that: The thermal conductive filler uses one of boron nitride and graphene, and the mass fraction of the filler is 10% to 15% of the total mass of the conductive adhesive.

10. The method for packaging a smart card chip on a strip according to claim 1, characterized in that: The contact resistance is tested by a four-probe method.